PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, LEVERAGE DAN PENGUNGKAPAN MEDIA TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY PADA PERUSAHAAN MANUFAKTUR DI SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2016-2018 - Catur Oktaviani; Rispantyo Rispantyo; Djoko Kristianto (Universitas Slamet Riyadi, 2020)
Corporate Social Responsibility Disclosure is a firm commitment toparticipate in the sustainable economic development to improve the quality of lifeand give benefit for environment or the company itself, the local community andsociety. The framework of social responsibility reporting concept which can beused is the Global Reporting Initiative (GRI) in the form of sustainability reports.However only few companies have disclosed their social responsibility activitiesin a sustainability report. The purpose of this study is to examine the influence offirm size, probability, leverage and media exposure to corporate socialresponsibility disclosure. The dependent variable is corporate socialresponsibility. Independent variable are firm size, profitability, leverage andmedia exposure. This study was used secondary data from annual reports andfinancial reports of manufacturing companies which were listed in Indonesiastock exchange in 2016-2018 period. Samples were 60 manufacturing companies.This study used purposive sampling method and multiple linear regression as theanalysis method. Before being conducted by regression test, it was examined byusing the classical assumption test. The results of this study indicate that firm sizeand profitability not have significant influence to the CSR disclosure meanwhilethe leverage and media exposure have a positive significant influence to CSRdisclosure.